Acetone sensor based on metal ion doped cerium dioxide aerogel, preparation method and application of acetone sensor in acetone detection

Through metal ion doping alumina aerogel materials, the problems of complex preparation and insufficient sensitivity performance of ceria materials are solved, and efficient, simple preparation and high-performance acetone sensors are achieved, suitable for mass production and rapid detection.

CN119125243AActive Publication Date: 2024-12-13JILIN UNIVERSITY
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411277472.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-12
Publication Date
2024-12-13
Estimated Expiration
2044-09-12

AI Technical Summary

Technical Problem

The existing ceria materials are made in the field of gas sensors with complex preparation methods, low yields, and need to improve sensitivity performance, making it difficult to meet the needs of efficient detection.

Method used

A metal ion-doped alumina aerogel material is used to prepare a porous aerogel through thermal decomposition of cerium ammonium nitrate, glucose and metal nitrate. It combines ceramic tubes and nickel-chromium alloy heating coils to form a resistive acetone sensor. Porous structure and metal ion doping improve gas-sensitive performance.

Benefits of technology

It realizes an efficient and simple preparation method, improves the stability and gas-sensitive performance of the material, has an ultra-fast response recovery rate, and is suitable for mass production and acetone detection.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0005040655290000011
    Figure HDA0005040655290000011
  • Figure HDA0005040655290000012
    Figure HDA0005040655290000012
  • Figure HDA0005040655290000021
    Figure HDA0005040655290000021
Patent Text Reader

Abstract

The invention discloses an acetone sensor based on metal ion doped cerium dioxide aerogel, a preparation method and application of the acetone sensor in acetone detection, and belongs to the technical field of gas sensors. The sensor consists of an Al2O3 ceramic tube substrate, two parallel and independent annular Au electrodes coated on the outer surface of the Al2O3 ceramic tube substrate, gas sensitive films coated on the outer surface of the Al2O3 ceramic tube and the annular Au electrodes, and a nichrome heating coil penetrating through the inside of the Al2O3 ceramic tube. The material of the gas sensitive film is metal ion doped cerium dioxide aerogel with a porous structure, metal ions are cobalt, copper, manganese and the like, and the abundant porous structure is beneficial to increasing the number of surface active sites of the material and increasing the diffusion speed of gas molecules and reaction products; the sensor based on the metal ion doped cerium dioxide aerogel prepared by the invention has an ultrafast response recovery rate to acetone, and has a good application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of gas sensors, and in particular relates to an acetone sensor based on metal ion-doped ceria aerogel, a preparation method and application of the sensor in acetone detection. Background Art

[0002] As a commonly used organic chemical reagent, acetone is an indispensable solvent or important raw material in the fields of organic chemical synthesis and chemical production. However, acetone is highly volatile and will spread and diffuse in the atmospheric environment. Once acetone gas enters the human body, it will cause serious harm to health. Therefore, acetone has become a typical toxic and harmful gas. In addition, acetone gas is also a special gas in the exhaled breath of the human body, and its concentration presents different values ​​with the difference in physical health. For example, the acetone concentration in the exhaled breath of healthy people is about 0.3-0.9ppm, while the acetone concentration in the exhaled breath of diabetic patients is generally greater than 1.8ppm. Therefore, detecting the concentration of acetone in exhaled breath provides a new idea for non-invasive diagnosis of diabetes. As mentioned above, accurately measuring the concentration of acetone gas in the gas environment has important research significance and practical value in the fields of environmental monitoring and medical diagnosis.

[0003] In recent years, resistive gas sensors based on semiconductor oxides have received extensive attention from academia and industry. Due to their advantages of low cost, simple structure, and easy device integration, they have become a rapidly developing gas detection technology, which is expected to overcome the bottleneck problems of traditional analytical instruments in gas detection, such as large size, complex operation, and inability to detect online. Ceria, as a typical n-type semiconductor material, is a type of catalyst or catalyst carrier with excellent performance in the field of catalysis. Generally speaking, the sensitivity of gas sensors depends on the redox process between target gas molecules and sensitive materials. Therefore, ceria materials with excellent catalytic performance have potential application value in the field of gas sensors. However, the current preparation method of ceria materials still has the disadvantages of complex operation and low yield. At the same time, the gas sensitivity of ceria materials needs to be further improved. Therefore, developing simple and efficient preparation technology and improving the sensitivity of ceria materials are important issues that need to be solved urgently. Summary of the invention

[0004] In view of the deficiencies in the prior art, the purpose of the present invention is to utilize the rich void structure of aerogel materials and the doping effect of metal ions to improve the gas-sensitive performance of ceria to acetone, thereby providing an acetone sensor based on metal ion-doped ceria aerogel, a preparation method and its application in acetone detection, so as to solve the problems existing in the background technology.

[0005] The acetone sensor based on metal ion doped ceria aerogel of the present invention is a ceramic tube structure, which is composed of an Al2O3 ceramic tube substrate, two parallel and mutually independent annular Au electrodes coated on the outer surface of the Al2O3 ceramic tube substrate, a gas sensitive film coated on the outer surface of the Al2O3 ceramic tube and the annular Au electrodes, and a nickel-chromium alloy heating coil passing through the inside of the Al2O3 ceramic tube; the material of the gas sensitive film is metal ion doped ceria aerogel, and the preparation steps are as follows:

[0006] (1) adding 0.5-1.0 g of ammonium cerium nitrate powder to 1.0-5.0 mL of water, stirring at room temperature for 5-10 min to obtain an aqueous solution of ammonium cerium nitrate;

[0007] (2) adding 0.25-1.0 g of glucose to the aqueous solution of ammonium cerium nitrate obtained in step (1), stirring at room temperature for 5-10 min to obtain a mixed aqueous solution of ammonium cerium nitrate and glucose;

[0008] (3) adding 1.0-3.0 mL, 2.0-5.0 mg / mL of a metal nitrate aqueous solution (manganese nitrate, copper nitrate, cobalt nitrate, etc.) to the mixed aqueous solution of ammonium cerium nitrate and glucose obtained in step (2), stirring at room temperature for 5-10 min to obtain a mixed aqueous solution of metal nitrate, ammonium cerium nitrate and glucose;

[0009] (4) placing the mixed aqueous solution of metal nitrate, ammonium cerium nitrate and glucose obtained in step (3) in a constant temperature drying oven, and drying at 100 to 120° C. for 30 to 50 minutes to obtain a solid mixture of metal nitrate, ammonium cerium nitrate and glucose;

[0010] (5) calcining the solid mixture of metal nitrate, ammonium cerium nitrate and glucose obtained in step (4) at 500-600° C. for 2-4 hours to obtain the metal ion-doped cerium dioxide aerogel.

[0011] The Al2O3 ceramic tube used in the present invention has a length of 3-5 mm, an outer diameter of 1.1-1.3 mm, and an inner diameter of 0.7-0.9 mm; the nickel-chromium alloy heating coil provides a suitable working temperature for the sensor, and the resistance of the heating coil is 30-40 Ω; the width of the annular Au electrode is 0.7-0.9 mm, the spacing between the two Au electrodes is 1.7-1.9 mm, the thickness of the Au electrode is 0.05-0.08 mm, and the thickness of the gas sensitive film is 180-220 μm; before and after the gas sensitive film contacts the gas to be measured, its resistance will change, and the sensitivity of the sensor can be obtained by measuring the change in resistance between the two annular Au electrodes. The sensitivity is calculated by dividing the resistance value of the two annular Au electrodes in the air by the resistance value thereof in the target gas.

[0012] The method for preparing a resistive acetone sensor based on metal ion-doped ceria aerogel according to the present invention comprises the following steps:

[0013] (1) mixing metal ion-doped cerium dioxide aerogel and deionized water in a mass ratio of 3 to 5:1, and grinding them into a paste slurry; coating the slurry on the surface of an Al2O3 ceramic tube having two parallel and separate annular Au electrodes on the outer surface;

[0014] (2) baking the device obtained in step (1) under an infrared lamp for 20 to 40 minutes, and after the sensitive material is dried, passing a nickel-chromium alloy heating coil with a resistance value of 30 to 40 Ω through the interior of the Al2O3 ceramic tube as a heating wire, and then welding and packaging it according to the indirect heating gas sensor;

[0015] (3) The device obtained in step (2) is subjected to aging treatment at 280-320° C. for 8-12 hours, thereby obtaining the resistive acetone sensor based on metal ion-doped ceria aerogel.

[0016] The advantages of the present invention are:

[0017] 1) The metal ion-doped cerium dioxide aerogel in the present invention has a porous structure, and the rich porous structure is beneficial to increasing the number of surface active sites of the material and increasing the diffusion rate of gas molecules and reaction products;

[0018] 2) The metal ion-doped cerium dioxide aerogel in the present invention has good crystallinity, so that the material has excellent stability;

[0019] 3) In the present invention, the gas generated by the thermal decomposition of precursors such as nitrate, ammonium cerium nitrate, glucose, etc. is used as a template to prepare a metal ion-doped cerium dioxide aerogel with a porous structure, without the need to use expensive organic compounds as templates;

[0020] 4) The present invention adopts a direct calcination method to prepare metal ion-doped cerium dioxide aerogel, which is simple, efficient, high in yield, and suitable for mass production;

[0021] 5) The sensor based on metal ion-doped cerium dioxide aerogel prepared in the present invention has an ultrafast response recovery rate to acetone and has good application prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 is a scanning electron microscope photograph of the cobalt-doped cerium dioxide aerogel prepared in Example 1;

[0023] Figure 2 1 is a nitrogen adsorption curve (a) and a pore distribution curve (b) of the cobalt-doped ceria aerogel prepared in Example 1;

[0024] Figure 3 is the X-ray diffraction pattern of the cobalt-doped cerium dioxide aerogel prepared in Example 2;

[0025] Figure 4 is the X-ray diffraction pattern of the copper-doped ceria aerogel prepared in Example 3;

[0026] Figure 5 is the X-ray diffraction pattern of the manganese-doped ceria aerogel prepared in Example 5;

[0027] Figure 6 is the response recovery curve of the acetone sensor based on cobalt-doped ceria aerogel prepared in Example 2 to 500 ppm acetone at 290°C;

[0028] Figure 7 is the response recovery curve of the acetone sensor based on copper-doped ceria aerogel prepared in Example 3 to 500 ppm acetone at 290°C;

[0029] Figure 8 This is the response recovery curve of the acetone sensor based on manganese-doped ceria aerogel prepared in Example 5 to 500 ppm acetone at 290°C

[0030] Fig. 9 is the response recovery curve of the acetone sensor based on cobalt-doped ceria aerogel prepared in Example 2 to 100-600 ppm acetone at 290°C;

[0031] Fig.10 These are six continuous response recovery curves of the acetone sensor based on cobalt-doped ceria aerogel prepared in Example 2 to 500 ppm acetone at 290°C.

[0032] The scanning electron microscope photo of the cobalt-doped cerium dioxide aerogel prepared in Example 1 is as follows: Figure 1 As shown, it can be seen that the cobalt-doped ceria aerogel is composed of a typical lamellar structure. There are a large number of gaps between the lamellar layers, which are assembled to form an aerogel structure. In addition, a large number of pore structures are also distributed in the plane of the cobalt-doped ceria lamellar structure, indicating that the cobalt-doped ceria aerogel prepared by the present invention has a unique porous structure.

[0033] The nitrogen adsorption-desorption curve and pore distribution curve of the cobalt-doped cerium dioxide aerogel prepared in Example 1 are as follows: Figure 2 As shown. Cobalt-doped ceria aerogels show obvious adsorption behavior in the high specific pressure region, indicating that they have a porous structure. The pore distribution curve also further illustrates that there are mesoporous structures with a size of 2 to 10 nm in cobalt-doped ceria aerogels;

[0034] The X-ray diffraction pattern of the cobalt-doped cerium dioxide aerogel prepared in Example 2 is as follows: Figure 3 As shown, it can be seen that the cobalt-doped ceria aerogel gives eight obvious peaks at 28.55°, 33.09°, 47.53°, 56.34°, 59.15°, 69.49°, 76.77°, and 79.06°, which belong to the characteristic crystal diffraction peaks of ceria. In addition, the intensity of these diffraction peaks is high and the peaks are narrow, indicating that the prepared cobalt-doped ceria aerogel has good crystallinity. Figure 3 No diffraction peak belonging to cobalt oxide was observed, indicating that the cobalt element was doped into the cerium dioxide lattice in the form of ions.

[0035] The X-ray diffraction pattern of the copper-doped cerium dioxide aerogel prepared in Example 3 is as follows: Figure 4 As shown, it can be seen that the copper-doped ceria aerogel has the same crystal structure as ceria and maintains good crystallinity, indicating that the doping of copper ions does not change the crystal structure of ceria. Since copper ions are distributed in the lattice of ceria in the form of ion doping, no diffraction peaks belonging to metallic copper or copper oxide are observed;

[0036] The X-ray diffraction pattern of the manganese-doped cerium dioxide aerogel prepared in Example 5 is as follows: Figure 5 As shown, it can be seen that the manganese-doped ceria aerogel also maintains a good crystal structure that is the same as that of ceria; in addition, Figure 5 No diffraction peaks belonging to manganese and manganese oxide were observed, which is because manganese ions are uniformly doped into the cerium dioxide lattice.

[0037] The response recovery transient curve of the acetone gas sensor based on cobalt-doped ceria aerogel prepared in Example 2 to 500 ppm acetone at 290°C is as follows: Figure 6 It can be seen that the sensor has good response recovery characteristics to acetone, and has a fast response and recovery rate, with a response time of 5.5s.

[0038] The recovery time is 12.5s;

[0039] The response recovery transient curve of the acetone gas sensor based on copper-doped ceria aerogel prepared in Example 3 to 500 ppm acetone at 290°C is as follows: Figure 7 As shown. It can be seen that the sensor also exhibits fast response recovery characteristics to acetone, with a response time of 37.1s and a recovery time of 21.5s;

[0040] The response recovery transient curve of the acetone gas sensor based on manganese-doped ceria aerogel prepared in Example 5 to 500 ppm acetone at 290°C is as follows: Figure 8As shown. It can be seen that the sensor shows good response recovery characteristics to acetone, with a response time of 17.1s and a recovery time of 12.5s;

[0041] The dynamic resistance response curve of the acetone sensor based on cobalt-doped ceria aerogel prepared in Example 2 to 100-600 ppm acetone at 290°C is shown in FIG. Fig. 9 It can be seen that with the increase of acetone concentration, the response value of the sensor gradually increases. At the same time, the sensor has fast response and recovery characteristics to acetone of different concentrations, and the detection limit of acetone is 100ppm;

[0042] The response repeatability curve of the acetone sensor based on cobalt-doped ceria aerogel prepared in Example 2 to 500 ppm acetone at 290°C is shown in FIG. Fig.10 It can be seen that the Co-doped Ceria aerogel based sensor shows a stable and repetitive response when repeatedly exposed to 500 ppm acetone, indicating that the sensor has excellent repeatability. DETAILED DESCRIPTION

[0043] The present invention is further described below with reference to the accompanying drawings and embodiments.

[0044] Example 1

[0045] (1) adding 0.5 g of ammonium cerium nitrate powder to 1.0 mL of water and stirring for 5 min at room temperature to obtain an aqueous solution of ammonium cerium nitrate;

[0046] (2) adding 1.0 g of glucose to the aqueous solution of ammonium cerium nitrate obtained in step (1), stirring at room temperature for 5 min to obtain a mixed aqueous solution of ammonium cerium nitrate and glucose;

[0047] (3) adding 3.0 mL of a 2.0 mg / mL aqueous solution of cobalt nitrate to the mixed aqueous solution of ammonium cerium nitrate and glucose obtained in step (2), and stirring at room temperature for 5 min to obtain a mixed aqueous solution of cobalt nitrate, ammonium cerium nitrate and glucose;

[0048] (4) placing the mixed aqueous solution of cobalt nitrate, ammonium cerium nitrate and glucose obtained in step (3) in a constant temperature drying oven and drying at 100° C. for 50 min to obtain a solid mixture of cobalt nitrate, ammonium cerium nitrate and glucose;

[0049] (5) calcining the solid mixture of cobalt nitrate, ammonium cerium nitrate and glucose obtained in step (4) at 600° C. for 4 h to obtain a cobalt ion-doped cerium dioxide aerogel material with a product mass of 0.16 g;

[0050] (6) The cobalt ion-doped cerium dioxide aerogel material prepared in step (5) is mixed with deionized water in a mass ratio of 3:1, and ground into a paste slurry, which is then coated on the surface of an Al2O3 ceramic tube with two parallel, annular and separate gold electrodes on the outer surface. Baking under an infrared lamp for 20 minutes, a sensitive film based on cobalt ion-doped cerium dioxide aerogel is obtained on the surface of the ceramic tube, and the thickness of the sensitive film is 180 μm; then a nickel-chromium alloy heating coil with a resistance value of 30Ω is passed through the Al2O3 ceramic tube as a heating wire, and finally welded and packaged according to the indirect heating gas sensor; the length of the Al2O3 ceramic tube is 3 mm, the outer diameter is 1.1 mm, and the inner diameter is 0.7 mm; the width of the annular Au electrode is 0.7 mm, the distance between the two electrodes is 1.7 mm, and the thickness of the Au electrode is 0.05 mm;

[0051] (7) The acetone gas sensor based on the cobalt ion-doped cerium dioxide aerogel material obtained in step (6) is aged at 280° C. for 12 hours to complete the aging treatment of the gas sensor, thereby obtaining a resistive acetone sensor based on the cobalt ion-doped cerium dioxide aerogel material.

[0052] Example 2

[0053] (1) adding 0.6 g of ammonium cerium nitrate powder to 1.0 mL of water and stirring for 10 min at room temperature to obtain an aqueous solution of ammonium cerium nitrate;

[0054] (2) adding 1.0 g of glucose to the aqueous solution of ammonium cerium nitrate obtained in step (1), stirring at room temperature for 5 min to obtain a mixed aqueous solution of ammonium cerium nitrate and glucose;

[0055] (3) adding 3.0 mL of a 2.0 mg / mL cobalt nitrate solution to the mixed aqueous solution of ammonium cerium nitrate and glucose obtained in step (2), and stirring at room temperature for 5 min to obtain a mixed aqueous solution of cobalt nitrate, ammonium cerium nitrate and glucose;

[0056] (4) placing the mixed aqueous solution of cobalt nitrate, ammonium cerium nitrate and glucose obtained in step (3) in a constant temperature drying oven and drying at 100° C. for 50 min to obtain a solid mixture of cobalt nitrate, ammonium cerium nitrate and glucose;

[0057] (5) calcining the solid mixture of cobalt nitrate, ammonium cerium nitrate and glucose obtained in step (4) at 600° C. for 3 h to obtain a cobalt ion-doped cerium dioxide aerogel material with a product mass of 0.19 g;

[0058] (6) The cobalt ion-doped cerium dioxide aerogel material prepared in step (5) is mixed with deionized water in a mass ratio of 3:1, and ground into a paste slurry, which is then coated on the surface of an Al2O3 ceramic tube with two parallel, annular and separate gold electrodes on the outer surface. Baking under an infrared lamp for 20 minutes, a sensitive film based on cobalt ion-doped cerium dioxide aerogel is obtained on the surface of the ceramic tube, and the thickness of the sensitive film is 180 μm; then a nickel-chromium alloy heating coil with a resistance value of 30Ω is passed through the Al2O3 ceramic tube as a heating wire, and finally welded and packaged according to the indirect heating gas sensor; the length of the Al2O3 ceramic tube is 3 mm, the outer diameter is 1.1 mm, and the inner diameter is 0.7 mm; the width of the annular Au electrode is 0.7 mm, the distance between the two electrodes is 1.7 mm, and the thickness of the Au electrode is 0.05 mm;

[0059] (7) The acetone gas sensor based on the cobalt ion-doped cerium dioxide aerogel material obtained in step (6) is aged at 280° C. for 12 hours to complete the aging treatment of the gas sensor, thereby obtaining a resistive acetone sensor based on the cobalt ion-doped cerium dioxide aerogel material.

[0060] Example 3

[0061] (1) adding 0.7 g of ammonium cerium nitrate powder to 3.0 mL of water and stirring for 5 min at room temperature to obtain an aqueous solution of ammonium cerium nitrate;

[0062] (2) adding 0.5 g of glucose to the aqueous solution of ammonium cerium nitrate obtained in step (1), stirring at room temperature for 5 min to obtain a mixed aqueous solution of ammonium cerium nitrate and glucose;

[0063] (3) adding 2.0 mL, 2.0 mg / mL copper nitrate solution to the mixed aqueous solution of ammonium cerium nitrate and glucose obtained in step (2), stirring at room temperature for 5 min to obtain a mixed aqueous solution of copper nitrate, ammonium cerium nitrate and glucose;

[0064] (4) placing the mixed aqueous solution of copper nitrate, ammonium cerium nitrate and glucose obtained in step (3) in a constant temperature drying oven and drying at 110° C. for 40 min to obtain a solid mixture of copper nitrate, ammonium cerium nitrate and glucose;

[0065] (5) calcining the solid mixture of copper nitrate, ammonium cerium nitrate and glucose obtained in step (4) at 600° C. for 2 h to obtain a copper ion-doped cerium dioxide aerogel material with a product mass of 0.22 g;

[0066] (6) The copper ion-doped cerium dioxide aerogel material prepared in step (5) is mixed with deionized water in a mass ratio of 3:1, and ground into a paste slurry, and the slurry is applied to the surface of an Al2O3 ceramic tube with two parallel, annular and separate gold electrodes on the outer surface; baked under an infrared lamp for 20 minutes, and a sensitive film based on copper ion-doped cerium dioxide aerogel is obtained on the surface of the ceramic tube, and the thickness of the sensitive film is 180 μm; then a nickel-chromium alloy heating coil with a resistance value of 30 Ω is passed through the Al2O3 ceramic tube as a heating wire, and finally welded and packaged according to the indirect heating gas sensor; the length of the Al2O3 ceramic tube is 3 mm, the outer diameter is 1.1 mm, and the inner diameter is 0.7 mm; the width of the annular Au electrode is 0.7 mm, the distance between the two electrodes is 1.7 mm, and the thickness of the Au electrode is 0.06 mm;

[0067] (7) The acetone gas sensor made of the copper metal ion-doped ceria aerogel material obtained in step (6) is subjected to an aging treatment at 280° C. for 12 hours to complete the aging treatment of the gas sensor, thereby obtaining a resistive acetone sensor based on the copper ion-doped ceria aerogel material.

[0068] Example 4

[0069] (1) adding 0.8 g of ammonium cerium nitrate powder to 3.0 mL of water and stirring for 10 min at room temperature to obtain an aqueous solution of ammonium cerium nitrate;

[0070] (2) adding 0.5 g of glucose to the aqueous solution of ammonium cerium nitrate obtained in step (1), stirring at room temperature for 10 min to obtain a mixed aqueous solution of ammonium cerium nitrate and glucose;

[0071] (3) adding 2.0 mL of a 5.0 mg / mL copper nitrate solution to the mixed aqueous solution of ammonium cerium nitrate and glucose obtained in step (2), and stirring at room temperature for 10 min to obtain a mixed aqueous solution of copper nitrate, ammonium cerium nitrate and glucose;

[0072] (4) placing the mixed aqueous solution of copper nitrate, ammonium cerium nitrate and glucose obtained in step (3) in a constant temperature drying oven and drying at 110° C. for 40 min to obtain a solid mixture of copper nitrate, ammonium cerium nitrate and glucose;

[0073] (5) calcining the solid mixture of copper nitrate, ammonium cerium nitrate and glucose obtained in step (4) at 500° C. for 4 h to obtain a copper ion-doped cerium dioxide aerogel material with a product mass of 0.25 g;

[0074] (6) The copper ion-doped cerium dioxide aerogel material prepared in step (5) is mixed with deionized water in a mass ratio of 3:1, and ground into a paste slurry, which is then coated on the surface of an Al2O3 ceramic tube with two parallel, annular and separate gold electrodes on the outer surface. Baking under an infrared lamp for 20 minutes, a sensitive film based on copper ion-doped cerium dioxide aerogel is obtained on the surface of the ceramic tube, and the thickness of the sensitive film is 180 μm; then a nickel-chromium alloy heating coil with a resistance value of 30Ω is passed through the Al2O3 ceramic tube as a heating wire, and finally welded and packaged according to the indirect heating gas sensor; the length of the Al2O3 ceramic tube is 3 mm, the outer diameter is 1.1 mm, and the inner diameter is 0.7 mm; the width of the annular Au electrode is 0.7 mm, the distance between the two electrodes is 1.7 mm, and the thickness of the Au electrode is 0.06 mm;

[0075] (7) The acetone gas sensor made of the copper metal ion-doped ceria aerogel material obtained in step (6) is subjected to an aging treatment at 280° C. for 12 hours to complete the aging treatment of the gas sensor, thereby obtaining a resistive acetone sensor based on the copper ion-doped ceria aerogel material.

[0076] Example 5

[0077] (1) adding 0.9 g of ammonium cerium nitrate powder to 5.0 mL of water and stirring for 5 min at room temperature to obtain an aqueous solution of ammonium cerium nitrate;

[0078] (2) adding 0.25 g of glucose to the aqueous solution of ammonium cerium nitrate obtained in step (1), stirring at room temperature for 10 min to obtain a mixed aqueous solution of ammonium cerium nitrate and glucose;

[0079] (3) adding 1.0 mL of 2.0 mg / mL manganese nitrate solution to the mixed solution of ammonium cerium nitrate and glucose obtained in step (2), stirring at room temperature for 10 min to obtain a mixed aqueous solution of manganese nitrate, ammonium cerium nitrate and glucose;

[0080] (4) placing the mixed aqueous solution of manganese nitrate, ammonium cerium nitrate and glucose obtained in step (3) in a constant temperature drying oven and drying at 120° C. for 30 min to obtain a solid mixture of manganese nitrate, ammonium cerium nitrate and glucose;

[0081] (5) calcining the solid mixture of manganese nitrate, ammonium cerium nitrate and glucose obtained in step (4) at 500° C. for 3 h to obtain a manganese ion-doped cerium dioxide aerogel material with a product mass of 0.28 g;

[0082] (6) The manganese ion-doped cerium dioxide aerogel material prepared in step (5) is mixed with deionized water in a mass ratio of 3:1, and ground into a paste slurry, and the slurry is applied to the surface of an Al2O3 ceramic tube with two parallel, annular and separate gold electrodes on the outer surface. Bake under an infrared lamp for 20 minutes to obtain a sensitive film based on manganese ion-doped cerium dioxide aerogel on the surface of the ceramic tube, and the thickness of the sensitive film is 180μm; then a nickel-chromium alloy heating coil with a resistance value of 30Ω is passed through the Al2O3 ceramic tube as a heating wire, and finally welded and packaged according to the indirect heating gas sensor; the length of the Al2O3 ceramic tube is 3mm, the outer diameter is 1.1mm, and the inner diameter is 0.7mm; the width of the annular Au electrode is 0.7mm, the distance between the two electrodes is 1.7mm, and the thickness of the Au electrode is 0.08mm;

[0083] (7) The acetone gas sensor based on manganese ion-doped ceria aerogel material obtained in step (6) is aged at 280° C. for 12 hours to complete the aging treatment of the gas sensor, thereby obtaining a resistive acetone sensor based on manganese ion-doped ceria aerogel material.

[0084] Example 6

[0085] (1) adding 1.0 g of ammonium cerium nitrate powder to 5.0 mL of water and stirring for 10 min at room temperature to obtain an aqueous solution of ammonium cerium nitrate;

[0086] (2) adding 0.25 g of glucose to the aqueous solution of ammonium cerium nitrate obtained in step (1), stirring at room temperature for 10 min to obtain a mixed aqueous solution of ammonium cerium nitrate and glucose;

[0087] (3) adding 1.0 mL of a 5.0 mg / mL manganese nitrate solution to the mixed aqueous solution of ammonium cerium nitrate and glucose obtained in step (2), and stirring at room temperature for 10 min to obtain a mixed aqueous solution of manganese nitrate, ammonium cerium nitrate and glucose;

[0088] (4) placing the mixed aqueous solution of manganese nitrate, ammonium cerium nitrate and glucose obtained in step (3) in a constant temperature drying oven and drying at 120° C. for 30 min to obtain a solid mixture of manganese nitrate, ammonium cerium nitrate and glucose;

[0089] (5) calcining the solid mixture of manganese nitrate, ammonium cerium nitrate and glucose obtained in step (4) at 500° C. for 2 h to obtain a manganese ion-doped cerium dioxide aerogel material with a product mass of 0.32 g;

[0090] (6) The manganese ion-doped cerium dioxide aerogel material prepared in step (5) is mixed with deionized water in a mass ratio of 3:1, and ground into a paste slurry, and the slurry is applied to the surface of an Al2O3 ceramic tube with two parallel, annular and separate gold electrodes on the outer surface. Bake under an infrared lamp for 20 minutes to obtain a sensitive film based on manganese ion-doped cerium dioxide aerogel on the surface of the ceramic tube, and the thickness of the sensitive film is 180μm; then a nickel-chromium alloy heating coil with a resistance value of 30Ω is passed through the Al2O3 ceramic tube as a heating wire, and finally welded and packaged according to the indirect heating gas sensor; the length of the Al2O3 ceramic tube is 3mm, the outer diameter is 1.1mm, and the inner diameter is 0.7mm; the width of the annular Au electrode is 0.7mm, the distance between the two electrodes is 1.7mm, and the thickness of the Au electrode is 0.08mm;

[0091] (7) The acetone gas sensor based on manganese ion-doped ceria aerogel material obtained in step (6) is aged at 280° C. for 12 hours to complete the aging treatment of the gas sensor, thereby obtaining a resistive acetone sensor based on manganese ion-doped ceria aerogel material.

Claims

1. An acetone sensor based on metal ion doped ceria aerogel, comprising an Al2O3 ceramic tube substrate, two parallel and separate annular Au electrodes coated on the outer surface of the Al2O3 ceramic tube substrate, a gas sensitive film coated on the outer surface of the Al2O3 ceramic tube and the annular Au electrodes, and a nickel-chromium alloy heating coil passing through the interior of the Al2O3 ceramic tube; characterized in that: The material of the gas sensitive film is metal ion doped ceria aerogel, and its preparation steps are as follows: (1) adding 0.5-1.0 g of ammonium cerium nitrate powder to 1.0-5.0 mL of water, stirring at room temperature for 5-10 min to obtain an aqueous solution of ammonium cerium nitrate; (2) adding 0.25-1.0 g of glucose to the aqueous solution of ammonium cerium nitrate obtained in step (1), stirring at room temperature for 5-10 min to obtain a mixed aqueous solution of ammonium cerium nitrate and glucose; (3) adding 1.0-3.0 mL, 2.0-5.0 mg / mL of a metal nitrate aqueous solution to the mixed aqueous solution of ammonium cerium nitrate and glucose obtained in step (2), stirring at room temperature for 5-10 min to obtain a mixed aqueous solution of metal nitrate, ammonium cerium nitrate and glucose; (4) placing the mixed aqueous solution of metal nitrate, ammonium cerium nitrate and glucose obtained in step (3) in a constant temperature drying oven, and drying at 100 to 120° C. for 30 to 50 minutes to obtain a solid mixture of metal nitrate, ammonium cerium nitrate and glucose; (5) calcining the solid mixture of metal nitrate, ammonium cerium nitrate and glucose obtained in step (4) at 500-600° C. for 2-4 hours to obtain the metal ion-doped cerium dioxide aerogel.

2. An acetone sensor based on metal ion doped ceria aerogel as claimed in claim 1, characterized in that: The metal nitrate is one or more of manganese nitrate, copper nitrate or cobalt nitrate.

3. The acetone sensor based on metal ion doped ceria aerogel according to claim 1, characterized in that: The thickness of the gas sensitive film is 180-220 μm.

4. The acetone sensor based on metal ion doped ceria aerogel according to claim 1, characterized in that: The length of the Al2O3 ceramic tube is 3-5 mm, the outer diameter is 1.1-1.3 mm, and the inner diameter is 0.7-0.9 mm; the resistance of the nickel-chromium alloy heating coil is 30-40 Ω; the width of the annular Au electrode is 0.7-0.9 mm, the distance between the two Au electrodes is 1.7-1.9 mm, and the thickness of the Au electrode is 0.05-0.08 mm.

5. A method for preparing a resistive acetone sensor based on metal ion-doped ceria aerogel according to any one of claims 1 to 4, comprising the following steps: (1) mixing metal ion-doped cerium dioxide aerogel and deionized water in a mass ratio of 3 to 5:1, and grinding them into a paste slurry; coating the slurry on the surface of an Al2O3 ceramic tube having two parallel and separate annular Au electrodes on the outer surface; (2) baking the device obtained in step (1) under an infrared lamp for 20 to 40 minutes, and after the sensitive material is dried, passing a nickel-chromium alloy heating coil with a resistance value of 30 to 40 Ω through the interior of the Al2O3 ceramic tube as a heating wire, and then welding and packaging it according to the indirect heating gas sensor; (3) The device obtained in step (2) is subjected to aging treatment at 280-320° C. for 8-12 hours, thereby obtaining the resistive acetone sensor based on metal ion-doped ceria aerogel.

6. Use of a resistive acetone sensor based on metal ion-doped ceria aerogel according to any one of claims 1 to 4 in acetone detection.

Citation Information

Patent Citations

  • Aerogel material composed of fibers and adhesive, and preparation method and application thereof

    CN107868270A

  • Acetone gas sensor based on porous CuFe2O4 microspherical sensitive material and preparation method of acetone gas sensor

    CN109001264A

  • Acetone sensor based on MoO3 / In2O3 composite sensitive material, preparation method and application thereof

    CN109470744A

  • TiO2 / SnO2 heterojunction aerogel, preparation method and application thereof and acetone gas sensor

    CN117623374A

  • Manufacture of gas sensor constitutional material

    JP1985071942A